Transcultural Italies : mobility, memory and translation - Burdett, Charles, 1966-; Polezzi, Loredana; Spadaro, Barbara (Transnational Italian cultures, 2020)
The history of Italian culture stems from multiple experiences of mobility and migration, which have produced a range of narratives, inside and outside Italy. This collection interrogates the dynamic nature of Italian identity and culture, focussing on the concepts and practices of mobility, memory and translation. It adopts a transnational perspective, offering a fresh approach to the study of Italy and of Modern Languages.